MEMBANGUN KARAKTER MAHASISWA MELALUI MATAKULIAH AL-ISLAM KEMUHAMMADIYAHAN (AIK) di UNIVERSITAS MUHAMMADIYAH SIDOARJO - Puspita Handayani; Ima Faizah; Mu’adz Mu’adz (Universitas Muhammadiyah Surakarta, 2020)
Al-Islam Kemuhammadiyahan (AIK) course is a spirit of Muhammadiyah colleges. In its implementation, AIK courses are taken by students in four semesters or at least 8 credits with a maximum of 12 credits. With the distribution model AIK1, 2, 3, and 4 in its implementation it has not been able to provide significant changes to the formation of student character. The indications are, there are still many students who are undisciplined, break the rules, still find dishonest behavior during exams, the low religious students seen from their active running prayer in congregation at the campus mosque, and clean living patterns in the campus environment. The formation of UMSIDA student character will be realized when there is a support program to build character, so the Al-Islam Kemuhammadiyahan Institute conducts a Character Education program for new students (PKMU) through several changes in the implementation model. This program is implemented as a form of AIK course mentoring.